Soberanías en conflicto: conservación y naciones indígenas en la Amazonía peruana - Merino, Roger (2022)
Indigenous organizations, international actors, and national authorities portray different images of the relationship between ‘Indigenous Peoples’ and the natural environment. Based on these images, these actors deploy ecological, economic, and security arguments to create or transform protected areas. By exploring three cases of conflicts over inception and management of protected areas in the Peruvian Amazon this paper maps the tensions around the different images and explores how indigenous organizations and state authorities - backed by international actors - engage with security, economic and ecological rationales from their own sovereignty standpoint. The paper argues that the State weakens indigenous political aspiration of sovereign territorial control by translating this agenda into depoliticized mechanisms and assumptions of modern international environmentalism, which ultimately limits their capacity to truly contribute to conservation goals. Rather, a ‘nation-building’ approach to conservation, by conceiving Indigenous Nations as sovereign partners in environmental management, might give environmental initiatives legitimacy.